(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
In a retrospective analysis of the materials of the forensic medical service, it was revealed that the improper provision of medical care in the activities of otolaryngologist and others had specific features. Defects in diagnosis and treatment prevailed by nature, which arose due to subjective reasons, more often in institutions of the prehospital and hospital stages, and in the outcome contributed to the onset of death or did not have a significant impact on the outcome